PENGARUH GUIDED INQUIRY LEARNING BERBANTUAN BOARD GAME TERHADAP KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR - Nurani Hadnistia Darmawan; Hilman Hilmawan; Nadia Agustiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science process skills are one of the competencies that must be mastered in learning to foster a scientific mindset and problem-solving abilities. These skills help to develop students who are critical, creative, innovative and ready to compete on a global scale. In reality, science process skills are still not optimally stimulated in science learning, which tends to focus solely on conceptual or theoretical teaching. One learning model that can enhance science process skills is guided inquiry. This study aims to determine the effect of guided inquiry learning assisted by the board game on the science process skills of primary school pupils. The design used in this study is a quasi-experimental design with a non-equivalent control group. The total sample size for the study was 54 pupils. Tests and questionnaires were used as data collection techniques. The results of the independent samples t-test showed that 0.00 < α = 0.05. This indicates that there is a significant effect of the implementation of guided inquiry learning supported by the board game on the science process skills of primary school pupils. Furthermore, the results of the questionnaire analysis regarding students’ responses to the implementation of guided inquiry learning were 98.52%, and those regarding the use of the board game as a learning tool were 99.63%. Both results indicate a positive response or interest from students in participating in the learning process.